ADENOSINE MONOPHOSPHATE–ACTIVATED PROTEIN KINASE PHOSPHORYLATION MEDIATED BY SIRTUIN 5 ALLEVIATES SEPTIC ACUTE KIDNEY INJURY. Issue 3 (19th March 2023) - Wang, Tingjie; Lin, Bo; Qiu, Weihuang; Yu, Binmei; Li, Jiaxin; An, Sheng; Weng, Lijun; Li, Yuying; Shi, Menglu; Chen, Zhongqing; Zeng, Zhenhua; Lin, Xianzhong; et al.
ABSTRACT: Background : Our previous studies have shown that ameliorating mitochondrial damage in renal tubular epithelial cells (RTECs) can alleviate septic acute kidney injury (SAKI). It is reported that AMPK phosphorylation (p-AMPK) could ameliorate mitochondrial damage in renal tissue and Sirtuin 5 (SIRT5) overexpression significantly enhanced the level of p-AMPK in bovine preadipocytes. However, the role of SIRT5-mediated phosphorylation of AMPK in SAKI needs to be clarified. Methods : WT/SIRT5 gene knockout mouse model of cecal ligation and puncture–induced SAKI and a human kidney 2 cell model of LPS-induced SAKI were constructed. An AMPK chemical activator and SIRT5 overexpression plasmid were used. Indexes of mitochondrial structure and function, level of p-AMPK, and expression of SIRT5 protein in renal tissue and RTECs were measured. Results : After sepsis stimulation, the p-AMPK level was decreased, mitochondrial structure was disrupted, and ATP content was decreased. Notably, an AMPK activator alleviated SAKI. Sirtuin 5 gene knockout significantly aggravated SAKI, while SIRT5 overexpression alleviated mitochondrial dysfunction after LPS stimulation, as manifested by the increase of p-AMPK level, the alleviation of mitochondrial structure damage, the restoration of ATP content, the decrease of proapoptotic protein expression, as well as the reduction of reactive oxygen species generation. Conclusions : Upregulation of SIRT5 expression can attenuate mitochondrial dysfunction in RTECs and alleviate SAKI by enhancing the phosphorylation of AMPK.